PH-Dependent Stability of Creatine Ethyl Ester: Relevance to Oral Absorption. (1st September 2013) - Gufford, Brandon T.; Ezell, Edward L.; Robinson, Dennis H.; Miller, Donald W.; Miller, Nicholas J.; Gu, Xiaochen; Vennerstrom, Jonathan L.
ABSTRACT Creatine ethyl ester hydrochloride (CEE) was synthesized as a prodrug of creatine (CRT) to improve aqueous solubility, gastrointestinal permeability, and ultimately the pharmacodynamics of CRT. We used high-performance liquid chromatography (HPLC) and proton nuclear magnetic resonance (NMR) to characterize the pH-dependent stability of CEE in aqueous solution and compared the permeability of CEE to CRT and creatinine (CRN) across Caco-2 human epithelial cell monolayers and transdermal permeability across porcine skin. CEE was most stable in a strongly acidic condition (half-life = 570 hours at pH 1.0) where it undergoes ester hydrolysis to CRT and ethanol. At pH ≥ 1.0, CEE cyclizes to CRN with the logarithm of the first order rate constant increasing linearly with pH. Above pH 8.0 (half-life = 23 sec) the rate of degradation was too rapid to be determined. The rate of degradation of CEE in cell culture media and simulated intestinal fluid (SIF) was a function of pH and correlated well with the stability in aqueous buffered solutions. The permeability of CEE across Caco-2 monolayers and porcine skin was significantly greater than that of CRT or CRN. The stability of CEE in acidic media together with its improved permeability suggests that CEE has potential for improved oral absorption compared to CRT.